2012
DOI: 10.1111/j.1460-2695.2012.01693.x
|View full text |Cite
|
Sign up to set email alerts
|

Life estimation model of a cantilevered beam subjected to complex random vibration

Abstract: An analytic methodology was developed to predict the fatigue life of a structure experiencing stationary, Gaussian random vibration excitation. This method allows the estimation of fatigue life using a frequency domain method, where only the input power spectral density and damping factor are required. The methodology uses linear elastic fracture mechanics for fatigue crack propagation and accounts for the frequency shifting that occurs due to fatigue crack evolution. Good results have been obtained comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…For structures subjected to random vibration, Ungar and others [9,12] have proposed that the pseudo velocity is proportional to stress. This applies to numerous geometries, including cantilevered beams.…”
Section: Theorymentioning
confidence: 98%
See 1 more Smart Citation
“…For structures subjected to random vibration, Ungar and others [9,12] have proposed that the pseudo velocity is proportional to stress. This applies to numerous geometries, including cantilevered beams.…”
Section: Theorymentioning
confidence: 98%
“…Although natural frequency shifting is a well documented phenomenon, the associated changing stress state is not. To this end a model was developed by Paulus et al [9] where the natural frequency shift and changing stress state were modeled. Time-to-failure (TTF) and natural frequency change were computed for complex random vibration environments using the input Power Spectral Density (PSD), damping and Linear Elastic Fracture Mechanics (LEFM).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of cracks in a structure is usually detected by adopting a linear approach through the monitoring of changes in the structure's dynamic response features [27][28][29]. Several studies have reported analytical and experimental results for vibration of cracked Euler-Bernoulli beams and the effects of surface cracks on fundamental frequencies and vibration modes of beams [30][31][32]. Few researchers uncovered nonlinear dynamic behavior of beam structures with single crack in the time history and frequency spectrum [33][34][35].…”
Section: Nonlinear Dynamics Of Undamaged and Damaged Structuresmentioning
confidence: 99%
“…No more precisions are given on the used fixture as in Hammami et al. [8], Paulus et al [9] or Li et al [10]. Only pictures of the experiments show the fixture used.…”
Section: Introductionmentioning
confidence: 99%